Az egyetemi ifjúság útkeresése az 1930-as években és 1940 körül - Ujváry, Gábor (Gerundium, 2019)
The Soulsearching of Hungarian Higher Education Students in the 1930s and 1940s. The study primarily focuses on the influential role of army brotherhood societies between the two world wars. The author outlines the ideological background and intellectual pursuit behind the movement. These brotherhood societies were so powerful, that in the 1930s and 1940s part of their activities manifested outside of the higher education environment. The societies actively engaged in politics, as much so, that their aim was to be part of the development of laws and the constitution. The author discusses the ambitions of both the radical right and the somewhat left wing youth establishments.